The Evaluation of Audio Steganography To Embed Image Files Using Encryption and Snappy Compression - Ilham Firman Ashari (AI Society & STMIK Indonesia, 2022)
Images are messages that can be kept secret, so security measures are needed. Techniques that can be used are cryptography and steganography. Steganography can be combined with cryptography to increase security. Images have a relatively large size; Therefore, a compression algorithm is needed. The compression algorithm used is lossless compression. MP3 audio is used as the cover media because it is the most popular audio file. In this study, aspects of imperceptibility, fidelity, recovery, payload, and robustness will be evaluated. The imperceptibility aspect is carried out by observing the RGB Histogram of the image and the audio frequency spectrum, the test results show that there is no significant difference between the audio before and after the image message is inserted. In the fidelity aspect, the PSNR result is above 30 dB. In the payload aspect, the file size after being encrypted with AES and RC4 is larger than just encoded using the base64 encoder. From the recovery aspect, the test results show a BER value of 0. Testing the robustness aspect by manipulating the bitrate, channel mode, and sample frequency, the test results show that the message cannot be extracted.